Food Injustice in Plural Societies - Iman Amanda Permatasari; Hasse Juba; Zuly Qodir; Muhammad Azhar (Universitas Pendidikan Ganesha, 2024)
It is said that meeting the food needs of the Indonesian people is not balanced, even though the level of food productivity is high. Famine conditions demonstrate this in several areas and low levels of food security compared to other countries. This article aims to explain the forms of food injustice in Plural Society, especially in Indonesia. This article is based on the argument that forms of food injustice in Indonesia occur because food distribution does not work well. This article is qualitative research, with data collection through document review. This article shows three forms of food injustice in Indonesia: inadequate public food consumption, the absence of special regulations for food distribution, and the emergence of a food waste culture in Indonesia. The conclusion of this article shows the reasons for food injustice in Indonesia, which occurs because food distribution does not work well, so the food supply chain cannot provide justice for food to the Indonesian people. This article contributes to comprehensive and in-depth knowledge about food injustice by highlighting food distribution issues and emphasizing the formulation of food distribution policies as a solution. This article is still limited to the secondary data used. A deeper study is needed through observations and interviews with parties understanding how food injustice occurs in Indonesia.